Character education strengthening (CES) mentoring for school-aged communities through out-of-classroom learning - Subur Subur; Muhammad Ghulam Zakiya; Muhammad Sa’ad; Rina Widianingrum; Feninda Septi Choirunisa; Elsa Calista Satya Paramesti (Community Empowerment, 2024)
Character education strengthening (CES) is a key factor in shaping children's personalities. Besides at home, character education should also be implemented in schools and social environments. In an effort to prepare the golden generation of 2045, the government is strengthening the character of the younger generation to have an advantage in the 21st-century global competition. This activity aims to instill character education during the Covid-19 pandemic by increasing the learning spirit, even though learning is done online and from home to avoid crowds. The method of implementing this activity is through participatory community empowerment using the participatory rural appraisal (PRA) model. Some of the achievements of this community service include: 1) outdoor activities or nature contemplation; 2) learning at TPA and Quran recitation to increase devotion to Allah SWT; 3) educational games outside the classroom to enhance nationalism and teamwork; 4) exploring students' potential and recognizing their intelligence through creativity contests; and 5) student learning motivation.